Fish oil supplemented for 9 months does not improve glycaemic control or insulin sensitivity in subjects with impaired glucose regulation: a parallel randomised controlled trial. Issue 1 (5th November 2015) - Clark, Louise F.; Thivierge, M. C.; Kidd, Claire A.; McGeoch, Susan C.; Abraham, Prakash; Pearson, Donald W. M.; Horgan, Graham W.; Holtrop, Grietje; Thies, Frank; Lobley, Gerald E.
Abstract: The effects of fish oil (FO) supplementation on glycaemic control are unclear, and positive effects may occur only when the phospholipid content of tissue membranes exceeds 14 % as n -3 PUFA. Subjects ( n 36, thirty-three completed) were paired based on metabolic parameters and allocated into a parallel double-blind randomised trial with one of each pair offered daily either 6 g of FO (3·9 g n -3 PUFA) or 6 g of maize oil (MO) for 9 months. Hyperinsulinaemic–euglycaemic–euaminoacidaemic (HIEGEAA) clamps (with [6, 6 2 H2 glucose]) were performed at the start and end of the intervention. Endogenous glucose production (EGP) and whole-body protein turnover (WBPT) were each measured after an overnight fast. The primary outcome involved the effect of oil type on insulin sensitivity related to glycaemic control. The secondary outcome involved the effect of oil type on WBPT. Subjects on FO ( n 16) had increased erythrocyte n -3 PUFA concentrations >14 %, whereas subjects on MO ( n 17) had unaltered n -3 PUFA concentrations at 9 %. Type of oil had no effect on fasting EGP, insulin sensitivity or total glucose disposal during the HIEGEAA clamp. In contrast, under insulin-stimulated conditions, total protein disposal ( P =0·007) and endogenous WBPT ( P =0·001) were both increased with FO. In an associated pilot study ( n 4, three completed), although n -3 PUFA in erythrocyte membranes increased to >14 % with the FO supplement, the enrichment in muscle membranes remained lower (8 %; P <0·001). In conclusion, long-term supplementation with FO, at amounts near the safety limits set by regulatory authorities in Europe and the USA, did not alter glycaemic control but did have an impact on WBPT.